PERKEMBANGAN BIOLOGIS, MOTORIK, KOGNITIF, DAN SOSIOEMOSIONAL (PADA MASA ANAK-ANAK) - Nur Thahirah Umajjah; Nia Angraeni; Asrika Asrika; Raudhatul Jannah; Aqila Rifkah; Wanni Agustin; Yunita Yunita; Intan Intan; Erna Erna; Bunga Bunga; Asisah Asisah; Indah Indah; Rahayu Wahyuni; Putri Syahwaliyah; Riska Amelia; Nurul Qolbi; Nur Ainun Annisa (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
Biological includes changes in body shape and size such as the growth of the brain, muscles, nervous system, bone structure, increase in height and weight. Motor development is a term used to describe the behavior of movements carried out by the human body. Cognitive development is the stages of changes that occur in the span of human life to understand, process information, solve problems and know something. Socio-emotional or emotional development in childhood is marked by the emergence of evaluative emotions that are recognized as pride, shame, and guilt, where the emergence of these emotions indicates that children have begun to understand and use social rules and norms to assess their behavior